Major improvement in the detection of microsatellite instability in colorectal cancer using HSP110 T17 E‐ice‐COLD‐PCR. Issue 3 (26th December 2017) - How‐Kit, Alexandre; Daunay, Antoine; Buhard, Olivier; Meiller, Clément; Sahbatou, Mourad; Collura, Ada; Duval, Alex; Deleuze, Jean‐François
Abstract: Every colorectal cancer (CRC) patient should be tested for microsatellite instability (MSI) to screen for Lynch syndrome. Evaluation of MSI status involves screening tumor DNA for the presence of somatic deletions in DNA repeats using PCR followed by fragment analysis. While this method may lack sensitivity due to the presence of a high level of germline DNA, which frequently contaminates the core of primary colon tumors, no other method developed to date is capable of modifying the standard PCR protocol to achieve improvement of MSI detection. Here, we describe a new approach developed for the ultra‐sensitive detection of MSI in CRC based on E‐ ice ‐COLD‐PCR, using HSP110 T17, a mononucleotide DNA repeat previously proposed as an optimal marker to detect MSI in tumor DNA, and an oligo(dT)16 LNA blocker probe complementary to wild‐type genotypes. The HT17 E‐ ice ‐COLD‐PCR assay improved MSI detection by 20–200‐fold compared with standard PCR using HT17 alone. It presents an analytical sensitivity of 0.1%–0.05% of mutant alleles in wild‐type background, thus greatly improving MSI detection in CRC samples highly contaminated with normal DNA. HT17 E‐ ice ‐COLD‐PCR is a rapid, cost‐effective, easy‐to‐implement, and highly sensitive method, which could significantly improve the detection of MSI in routine clinical testing. Abstract : Evaluation of MSI status in colorectal cancer involves screening tumor DNA for the presence of mutations in DNA repeats using PCR followed by fragment analysis. This method may lack sensitivity due to a high level of germline DNA contamination in the DNA of the tumor. Here we developed a new approach for the ultra‐sensitive detection of MSI in CRC based on HSP110 T17 and E‐ ice ‐COLD‐PCR, which improved MSI detection by 20–200‐fold compared to standard PCR using HT17 alone.